Economic Implication of Human - wildlife conflict in Lupande Game Management Area - Mambwe District, Eastern Province - Morgan, Chilembo; Nyanga , Progress (International Journal of Environmental Sciences, 2023)
Purpose: The study aimed at establishing the economic loss caused by Human - wildlife conflict amongst small scale farmers and government. To achieving the purpose, the research was mainly guided by three objectives. To estimate the economic value of damage in agriculture, to estimate the economic value related with control by killing of problematic animals and effectiveness of response strategies in addressing Human - wildlife conflict. Methodology: The study utilised descriptive research design where primary data was collected from key informants by applying semi-structured interview guide using convenient sampling. Purposive sampling during focus group discussion meetings using focus group discussion guides was administered in Human - wildlife conflict hot spot areas. The researcher further used secondary data to gain more understanding and gather adequate information about the area of study. Therefore, 70% of the affected households from Department of National Parks and Wildlife Human - wildlife conflict SMART raw data was used. Subsequently, Descriptive Statistics, using averages and totals to analyse quantitative data, was used while qualitative data was analysed using Content and Thematic Analysis. Findings: The summary of the results showed that economic damage in agriculture was quite enormous affecting farmers with K180, 317.00 being the highest in the damage range of 25-50 percent. Regarding the estimation on economic value related with problematic animal control by killing, it was established that the government of Zambia incurred huge revenue loss amounting to K 4,318,049.86 if such animals or trophies were sold. On the effectiveness of response strategies, the majority of the participants stated that few measures were put in place to solve Human - wildlife conflict. In Zambia, several researchers and scholars have reviewed Human - wildlife conflict phenomena. However, there has been no study that has sought to establish economic implication on small scale farmers and revenue loss to the government through control by killing of problematic animals. This study therefore seeks to fill this knowledge gap looking at estimation of economic implications of Human - wildlife conflict in the study area. Unique Contribution to Theory, Practice and Policy: The results of this study could influence formulation of appropriate mitigation measures and policies for wildlife conservation and revenue recovery from controlled by killed of such animals in Zambia.